Respuesta :

Only option d is the correct answer as x = 3 is a solution to the equation.

To solve this problem, we have to substitute the value of x into the equation and see if it is equal to zero.

Solution of an Equation

a)

[tex]3x+7 = x - 8[/tex]

when x = -6

substitute the value of x

[tex]3x+ 7 = x - 8\\x = -6\\3x-x = -8-7\\2x = -15\\2(-6) = -15\\-12 \neq -15[/tex]

equation (a) is wrong.

b)

[tex]-2x-8=-4x-1\\x = 3[/tex]

collect like terms and substitute for x

[tex]-2x-8=-4x-1\\x = 3\\-2x+4x= -1+8\\2x = 7\\2(3) = 7\\6\neq 7[/tex]

equation(b) is wrong

c)

[tex]-5x+7 = 2x - 14\\x = -8\\[/tex]

collect like terms and substitute for x

[tex]-5x+7 = 2x - 14\\x = -8\\7+ 14 = 2x + 5x\\21 = 7x\\21 = 7(-8)\\21 \neq -42[/tex]

d)

[tex]-(x-1)=4x-5-3x\\x = 3\\-(x-1) = 4x -5 -3x\\-x+1 = x- 5\\2x = 6\\2(3) = 6\\6 = 6\\[/tex]

From the above calculation, only option d is the correct answer as x = 3 is a solution to the equation.

Learn more on solutions of equation here;

https://brainly.com/question/16863577

Otras preguntas